2000
DOI: 10.1097/00043764-200001000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Toxicity due to Use of a Cosmetic Cream

Abstract: The Arizona Department of Health Services performed an investigation to determine the health effects associated with the use of a mercury-containing beauty cream. A urine test for mercury was offered to cream users who contacted the Arizona Department of Health Services. Those with urine mercury levels > 20 micrograms/L were offered clinical evaluation. Eighty-nine urine specimens were submitted for testing. Of these, 66 showed an elevated urine mercury level (> 20 micrograms/L), and 55 people were evaluated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 1 publication
1
37
1
Order By: Relevance
“…Although no major abnormalities were found, the urine mercury concentrations of former cream users declined over time from a median of 170 µg/L to 32 µg/L after an average of 139 days. 21 A New Mexico study also found median urine mercury concentrations among 25 users of the cream to be 4 times greater than among controls.…”
Section: Discussionmentioning
confidence: 95%
“…Although no major abnormalities were found, the urine mercury concentrations of former cream users declined over time from a median of 170 µg/L to 32 µg/L after an average of 139 days. 21 A New Mexico study also found median urine mercury concentrations among 25 users of the cream to be 4 times greater than among controls.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the general population is primarily exposed to mercury through diet and dental amalgam [21]. Some studies have reported women's use of skin-lightening creams and soaps [22,23] and its association with mercury exposure and this can be of significance for certain ethnic groups [24]. Exposure to metallic mercury alters oestrous cyclicity, but has no significant effect on ovulation, implantation or maintenance of first pregnancy during exposure of short duration in female rats [25].…”
Section: Discussionmentioning
confidence: 99%
“…Somehow, the entire population is exposed to some form of mercury primarily through drinking water, food or occupational exposure 1,2 . It has been reported that high levels of mercury exposure may occur via the use of skin lightening beauty creams, soaps and herbal drugs 3,4 . The toxic effects of mercury vary with the different chemical forms of mercury, the dose and the rate of exposure 2,5 .…”
Section: -Introductionmentioning
confidence: 99%